Nos limites do Jequitinhonha e Mucuri (MG): políticas públicas direcionadas ao espaço rural - Pereira, Claudinei da Silva [UNESP] (2015)
The performance of the Brazilian state along the 20th century and the beginning of 21st was ruled in structuring the necessary and favorable conditions for the expansion in the capitalism way of production in the national territory. By privileging spaces best to provide the capital for its consolidation, it renounced others of the possible improvements, and the consequences were the consolidation of unequal social, economic, and infrastructural structures. In Minas Gerais the capital forged in its expansion process, allied to the actuation of the State, mechanisms that reinforced the socio-spatial inequalities among the areas of the state. As form of integrating the areas that had been marginalized of the processes of structuring of the capital, the State through institutions in the state and federal levels regionalized the implementation of public policies. To understand the relationships between public policies and regionalization, in the ambit of this work, we intended to analyze starting from the delimited regionalization by the Superintendência de Desenvolvimento do Nordeste (SUDENE) and the Instituto de Desenvolvimento do Norte e Nordeste de Minas Gerais (IDENE) as the same public policy presents specificities in execution form, in case the municipality are in different areas. For that, we used as study cutting the municipalities of Caraí and Itaipé...